3era. Conferencia Mundial Trabajadores Azucareros, Santo Domingo, Rep. Dom., Mayo 5 al 8, 1987 : (ICCSASW (International Commission for the Coordination of Solidarity Among Sugar Workers), 1987)
(FENAZUCAR-CGT = National Federation of Sugar Workers). 1: Organizational aspects.